2006
DOI: 10.1530/rep-06-0040
|View full text |Cite
|
Sign up to set email alerts
|

The glycosylation of pregnancy-associated glycoproteins and prolactin-related protein-I in bovine binucleate trophoblast giant cells changes before parturition

Abstract: Binucleate trophoblast giant cells (BNC) in the bovine placenta produce glycoproteins, which are delivered into the mother after fusion of BNC with uterine epithelial cells. During most time of pregnancy, BNC produce pregnancy-associated glycoproteins (PAGs) and prolactin-related protein-I (PRP-I) with asparagine-linked lactosamine-type glycans terminating with N-acetyl-galactosamine. We show by lectin histochemistry that terminal N-acetyl-galactosamine (detected by Dolichos biflorus agglutinin, DBA) in placen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
0
8

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 36 publications
4
21
0
8
Order By: Relevance
“…In line with previous studies (Xie et al 1991, Zoli et al 1991, Patel et al 2004a, Klisch et al 2006, anti-PAG1 antibodies showed that the main PAG1 protein has an approximate molecular mass of 67 kDa and PAG1 has four potential sites for N-linked glycosylation (Xie et al 1991(Xie et al , 1995. We demonstrated that the progressive deglycosylation of native PAG1 resulted in two deglycosylated intermediates and the fully deglycosylated protein at the molecular size expected for the polypeptide.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In line with previous studies (Xie et al 1991, Zoli et al 1991, Patel et al 2004a, Klisch et al 2006, anti-PAG1 antibodies showed that the main PAG1 protein has an approximate molecular mass of 67 kDa and PAG1 has four potential sites for N-linked glycosylation (Xie et al 1991(Xie et al , 1995. We demonstrated that the progressive deglycosylation of native PAG1 resulted in two deglycosylated intermediates and the fully deglycosylated protein at the molecular size expected for the polypeptide.…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, we suggest that PAG2 is weakly glycosylated because the protein is synthesized by mononucleate cells (see below) that might lack the specific glycosylation machinery evidenced in binucleate cells (Klisch & Leiser 2003). Global changes to PAG glycosylation have been reported during gestation (Klisch et al 2006(Klisch et al , 2008 but the precise protein involved has not yet been identified. As PAGs display different patterns of expression during gestation, and because we showed that their glycan residues differ in size, it could be suggested that PAG might to some extent be involved in global changes to glycosylation.…”
Section: Discussionmentioning
confidence: 99%
“…These results revealed the composite profiles of key proteins involved in the abnormal placenta derived from SCNT, and suggested abnormalities in expression of these genes in the SCNT placenta, resulting in foetal losses after SCNT. Klisch et al (2006) observed changes in glycosylation in pregnancy-associated glycoproteins and prolactin-related protein I, synthesized in binuclear trophoblast giant cells. Western-blot and immunoenzymatic tests showed that before delivery in cows, the molecular mass of these proteins is reduced (1-2 kDa) in comparison with late pregnancy.…”
Section: Proteomics Of the Placenta And Livermentioning
confidence: 91%
“…The main reason for this finding may be an increase in the half-life of PAGs during pregnancy, resulting in its slower decrease after EM/FM in advanced pregnancies (Lobago et al, 2006;Zarrouk et al, 1999). Moreover, it has been shown that the half-life of PAGs increases from 1.8 to 6.6 days in advanced pregnancies (Lobago et al, 2006), which has been suggested to be caused by changes in the glycosylation patterns of PAGs, leading to a reduction in terminal N-acetyl-galactosamine, which is a potential ligand for this glycoprotein receptor, which plays a key role in the clearance of glycoproteins (Coombs et al, 2006;Klisch et al, 2006). EM/FM was most accurately diagnosed at a cut-off value of 1.2 with a SPE of 94%.…”
Section: Verification Experimentsmentioning
confidence: 99%